Standardization of an Effective Scarification and Germination Protocol for Strawberry Seeds That Is Useful for Gamic Propagation - Giammarco Giovanetti; Micol Marcellini; Valeria Pergolotti; Federica Mecozzi; Bruno Mezzetti; Franco Capocasa; Silvia Sabbadini (Horticulturae)
In strawberry (Fragaria × ananassa Duch.) breeding programs, seed dormancy adversely affects germination, resulting in delayed seedling emergence and low germination rates. This study investigated the best solution to enhance strawberry seed germination both in terms of efficiency and timing by evaluating the effect of three key factors: genotype, pre-sowing treatment, and germination medium. Chemical scarification treatment with the sulfuric acid of seeds from three different genotypes was optimized; treated seeds were placed to germinate on three germination media (Murashige and Skoog medium, peat, and filter paper) in a growth chamber. Seedlings obtained were acclimatized for evaluating post-acclimatization survival rate and possible phenotypic differences regarding seedling development. Chemical scarification treatment produced the best results, with germination rates of around 100% and the highest speed of germination compared to the not-treated controls. Indeed, more than 90% of the seeds germinated 14 days after sowing, regardless of the genotype or germination medium tested. Seedlings germinated on filter paper gave the poorest performances in terms of post-acclimatization survival rate and showed lower average plant height. In conclusion, it was demonstrated that excellent germination rates can be achieved through proper seed scarification, which is not genotype dependent; furthermore, when this method is combined with the correct germination medium, excellent seedling quality can be achieved.